The mitigation potential and cost efficiency of abatement-based payments for the production of short-rotation coppices in Germany. (October 2015) - Henseler, Martin; Röder, Norbert; Liebersbach, Horst; Kreins, Peter; Osterburg, Bernhard
Abstract: In Northern and Central Europe, short-rotation coppices (SRC) have become a profitable agricultural production alternative, particularly for marginal fields with suitable groundwater levels. Furthermore, the replacement of fossil fuels by the wood chips produced in SRC contributes to the mitigation of greenhouse gases (GHGs). Due to heterogeneous regional production conditions, the impacts on the economy, production and GHG mitigation are expected to vary widely by region. Several studies investigate the specific agronomic, environmental and economic aspects of SRC. However, only a few studies present a concise analysis of more than one or all of these aspects or evaluate SRC as a mitigation strategy. This study complements the existing literature by estimating the mitigation potential from SRC in Germany. It presents an integrated modeling approach that considers agronomic and economic aspects and investigates the mitigation potential and the abatement cost efficiency arising from abatement-based payments. The simulation of different payment scenarios indicates that SRC could mitigate up to 15% of the German agricultural sector's GHG emissions. The integrated model approach links a site model and the agro-economic model RAUMIS and can be regarded as a fruitful development for addressing SRC-related research questions as well as a promising base for further work. Highlights: Regionally explicit assessment of the economic potential of short rotation coppices. Model linkage between a site model and an agro-economic regional supply model. The developed model considers agronomic, agricultural and economic aspects of SRC. Evaluating the abatement cost efficiency under abatement based payments for SRC. SRC could mitigate up to 15% of the German agricultural sector's GHG emissions.